Review of radiation dose estimates in digital breast tomosynthesis relative to those in two-view full-field digital mammography. Issue 2 (April 2015) - Svahn, T.M.; Houssami, N.; Sechopoulos, I.; Mattsson, S.
Abstract We examined how radiation dose levels in digital breast tomosynthesis (DBT) differ from those used in 2-view full-field digital mammography (FFDM). Acquisition parameter settings and information on the average absorbed dose to the glandular tissues within the breasts were reviewed based on clinical studies that evaluated DBT and FFDM. Dose ratios (DDBT/DFFDM) were derived from imaging protocols, which included tomosynthesis in 1- or 2-views alone, and as an adjunct technique to FFDM. Stand-alone DBT was associated with a much lower to a slightly higher radiation dose compared to that of comparable FFDM units, as summarized in dose ratio ranges of 0.34–1.0 for 1-view DBT, and 0.68–1.17 for 2-view DBT. One of the lowest reported dose estimates was obtained using a photon-counting DBT unit (avg. 0.70 mGy/scan; range: 0.28–1.26 mGy). Breast doses for DBT combined with FFDM are summarized in dose ratio ranges of 1.03–1.5 for 1-view DBT plus FFDM, and 2.0–2.23 for 2-view DBT plus FFDM. In the latter of these settings, the dose was reduced by ∼45% when 2D-views, reconstructed from the DBT images ("synthetic 2D images"), were used as a substitute for FFDM. Stand-alone DBT operated at lower to slightly higher radiation doses in comparison to FFDM. For DBT combined with FFDM, radiation doses were elevated, at maximum by a factor ∼2 1/4 of that of FFDM alone. In this setting, a replacement of FFDM with synthetic 2D-views reduced the breast dose approximately by half, which has substantial implications for population screening programs.